Representations of Christmastide in Latin American Christmas Folk Songs: A Transitivity Analysis (Language Circle: Journal of Language and Literature, 2020)
Considered as the universal language, music has been historically a means of communication and personal expression about the inner and outer world of its creator, it is present in almost every social activity of human beings as in the habitual religious celebration of Christmas across the largely Catholic countries. Therefore, the present paper will provide a descriptive text analysis of ten traditional Latin American Christmas folk songs on the base of the transitivity system informed by the Hallidayan Systemic Functional Linguistics theory. To reach this goal, both a quantitative and qualitative research method approach was applied. Findings indicated that among the six analyzed transitivity process types, the material processes (32%) dominate the construal of the musical pieces, followed by the mental (23%), behavioral (18%), and relational realizations (13%) whereas the verbal and existential processes are relatively low all together representing an overall frequency of 14%. This reveals the singersâ€™ attempt to represent the Christmas season as a nostalgic time leap, an immediate enjoyment, and a rewarding exchange.Â